Desarrollo de carbón activado a partir de raquis de banano aplicado a la separación de oro en solución cianurada. - Cabrera Palacios, Washington Jair; Espinoza Aguirre, Martha Cristina (My University, 2024)
This study addresses the need to develop sustainable adsorbent materials for gold recovery in metallurgical processes. Activated carbon (AC) was developed from banana rachis, an abundant agricultural waste in banana-producing regions of Ecuador, through a double pyrolysis process and chemical activation with potassium hydroxide (KOH). Unactivated carbon (CSA) and a commercial activated carbon (CC) were compared with AC to evaluate their physical and chemical characteristics, as well as their adsorption capacity (Qe) toward the dicyanoaurate complex Au(CN)2- in a synthetic gold solution at different pH values (10, 11, 12). Characterization included Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), attrition tests, and determination of the zero-charge point (pHpzc). Adsorption analysis data were obtained using inductively coupled plasma optical emission spectroscopy (ICP-OES). KOH activation increased porosity and oxygenated functional groups in AC and improved its mechanical strength (22.3% weight loss) compared to CSA (55.8% weight loss), though it was lower than that of CC (10.5% weight loss). The pHpzc of AC was close to 10, indicating that at pH values below this, the material's surface would be positively charged, favoring the adsorption of the dicyanoaurate complex. Adsorption analysis results showed that AC achieved its highest adsorption capacity (Qe) of 12.75 mg/g at pH 12, which decreased as the pH decreased. At all tested pH levels, AC exhibited lower performance compared to CSA and CC. It is concluded that banana rachis is indeed a viable precursor for producing activated carbon capable of adsorbing gold from a cyanide solution, as evidenced by the results obtained in this study.
Este estudio aborda la necesidad de desarrollar materiales adsorbentes sostenibles para la recuperación de oro en procesos metalúrgicos. Se desarrolló un carbón activado (CA) a partir de raquis de banano, un residuo agrícola abundante en las regiones bananeras del Ecuador, mediante un proceso de doble pirólisis y activación química con hidróxido de potasio (KOH). El carbón sin activar (CSA) y un carbón activado comercial (CC) se compararon con el CA para evaluar sus características físicas y químicas, así como la capacidad adsorbente (Qe) hacia el complejo dicianoaurato Au(CN2)- en una solución sintética de oro a distintos valores de pH (10, 11, 12). La caracterización incluyó espectroscopía infrarroja por Transformada de Fourier (FTIR), difracción de rayos X (XRD), microscopía electrónica de barrido (SEM), pruebas de atricción y determinación del punto de carga cero (pHpzc). Los datos del análisis de adsorción fueron obtenidos por espectroscopía de emisión óptica de plasma inductivamente acoplado (ICP-OES). La activación con KOH incrementó la porosidad y grupos funcionales oxigenados en el CA y mejoró su resistencia mecánica (22.3% de pérdida de peso) con respecto a la del CSA (55.8% pp) pero a la vez fue menor que el CC (10.5% pp). El pHpzc del CA fue cercano a 10, indicando que, a pH inferiores, la superficie del material estará cargada positivamente favoreciendo la adsorción del complejo dicianoaurato. Los resultados del análisis de adsorción demostraron que el CA tuvo su mayor capacidad de adsorción Qe de 12.75 mg/g a pH 12 y disminuye a medida que baja el pH. En todos los pH analizados el CA mostró un rendimiento menor al del CSA y CC. Se concluye que el raquis de banano es, en efecto, un precursor viable para la obtención de carbón activado capaz de adsorber oro en una solución cianurada, como se evidencia en los resultados obtenidos en este estudio.
Keywords: CARBÓN ACTIVADO; RAQUIS DE BANANO; CARACTERIZACIÓN; ADSORCIÓN